The Effect of Smart City Applications on Smart City Life Inteniıon: The Moderating Role of Technology Anxiety - Yıldız, Bülent (Igdir University, 2024)
The human population living in cities in the world is constantly increasing. As a result of the increasing population, the use of digital technologies has become widespread to facilitate city life. The importance of a smart city has increased mainly due to the integration of artificial intelligence and Internet of Things technologies into cities. Therefore, this study aims to examine the effect of smart city applications on life intention and how technology anxiety moderates this effect. For this purpose, data were collected from 386 people using a questionnaire. The data were analysed with a structural equation model. As a result of the analyses, it was determined that smart public service, smart transportation and smart environmentalism practices significantly positively affect the intention to live in smart cities. As a result of the moderator analysis, it was found that technology anxiety has a moderating role in the effect of smart city applications on the intention to live in smart cities. Suggestions were made according to the research findings.
Keywords: smart cities; sustaniability; technology anxiety; akıllı şehir; sürdürülebilirlik; teknoloji kaygısı; Sürdürülebilir Kalkınma; Sustainable Development; 13. Climate action; 11. Sustainability